Pemanfaatan Daun Kelor (Moringa oleifera) untuk Bahan Dasar Pembuatan Cendol Jelly sebagai Minuman Tradisional - Adisty, Yuda; Vanesa, Tri; Wahyuni, Wahyuni (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Various types of plants that grow have the potential to provide benefits to human life, one of which is Moringa. Moringa is known as The Miracle Tree because it is proven to be a natural source of nutrients with medicinal properties. Utilization of local food ingredients that are relatively easy to obtain and have nutritional value, such as Moringa oleifera leaves, can be used as functional food products and sources of antioxidants. The research results show that the Moringa plant has various benefits both economically and healthily. Moringa is not only rich in nutrients but also has functional properties because this plant has properties and benefits for human health. Both the nutritional content and various active substances contained in this plant can be used for the benefit of living creatures and the environment. One part of the Moringa plant that has been widely studied for its nutritional content and uses for both food and health is the leaves. In this section there are a variety of nutrients, including calcium, iron, protein, vitamin A, vitamin B and vitamin C. The nutritional content of Moringa leaves is higher compared to other vegetables, namely in the range of 17.2 mg/100 g. The aim of this drink making activity is to utilize traditional ingredients which are rich in vitamins when consumed and are good for health. Keywords: Moringa leaves, active ingredients, vitamins, health.